Older People: A Counterweight to Consumer Hedonism in Society? Analysis of Consumption Preferences - Rapolienė, Gražina; Mikulionienė , Sarmitė (Socialinė teorija, empirija, politika ir praktika, 2021)
The Lithuanian consumer society is evolving, but we know little about it. On the one hand, previous research shows that it is a survival society that prioritizes functional needs, on the other hand, there are indications that a segment of consumers oriented towards self-expression is forming in Lithuania. Since consumption is both a consequence and a factor of class stratification, it is important to know whether (and how) it contributes to the strengthening of the social otherness of the group. The aim of this article is to find out whether (and how) consumption attitudes of older people differ from those of other age groups in Lithuania and what they are in the context of consumption values. In this study we analyzed the data of the representative Lithuanian population survey TNS Atlas (2012, N = 1847), divided into age groups (15–29, 30–44, 45–59, and 60–75 years). One-way analysis of variance (ANOVA) was performed for the comparison of consumption preferences, post hoc criteria and Spearman coefficient were applied, and the typology of values was used for the analysis of the content of statements. The results of this research showed that consumption attitudes of the Lithuanian population are not highly differentiated according to age, the attitudes of the oldest respondents (60–75 years old) differ little from others. The entire population aged 45–75 is more characterized by a combination of conservative and altruistic-ecological attitudes than the younger ones (18–44 years old), less characterized by openness to innovation and the pursuit of social self-enhancement. Although the differences in attitudes according to age are not bright in quantitative terms, in terms of content, there is a noticeable detachment of the older population from the refined consumer community.